The Understanding of BMT’s Practitioners of the PSAK No. 59 (The Accounting of Shari’ah Banking) on The Recognition and Measurement of Funding Products - Eny Iroh Hayati (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The objective of this research is to explore BMT practitioners’ understanding of the SPAK No. 59 on the Accounting of Shari’ah Banking for funding products. For this reason, the research is conducted by descriptive method. Field research using quantitative approach is also used. However, qualitative approach is also used to explore and to clarify as well as to compare between the concept and the real situation. The population used in this study are members of PUSKOP¬SYAH DIY, and the subjects of this research are the managers and accounting staffs of these BMTs. The sample consists of 30% of 80 active members. However, since the magnitude of each sub-population is different, proportional sampling method is used to determine the number of sample taken from each sub-population, and purposive sampling method is used as the sampling method. The independent variables used in this research are age, educational background, length of time working in BMT, and frequency of training or workshop joined by the subjects. Meanwhile, the dependent variable in this research is the BMT practitioners’ understanding about SPAK No. 59 for funding product. Data gathering methods used in this research were questionnaire, field observation and interview. Meanwhile, data analyses for this study include descriptive statistical analysis and inferential statistical analysis. Keywords: accounting, PSAK No. 59, understanding, practitioners of BMT